Penilaian Tata Kelola Teknologi Informasi Pada Institusi Pendidikan Tinggi Menggunakan COBIT 2019 - Pratiwindya Pratiwindya; Astari Retnowardhani (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
Information Technology (IT) Governance has an important role in managing and optimizing IT resources to support the achievement of the organization's vision and mission. In the higher education, the use of IT is needed to create and improve the quality of educational services. However, IT investments often made by many universities and colleges do not provide maximum benefits for the continuity of existing education services. Therefore, it is necessary to conduct an assessment of IT Governance at various universities and colleges in order to find out the level of capabilities and gaps that generally occurs. This research is a literature study that has the aim of analyzing IT Governance at various universities and colleges with reference to COBIT 2019.The research is conducted using Systematic Literature Review (SLR) method to answer Research Questions (RQ), namely RQ1 about the type of publication journal and article publication year, RQ2 about the domain of focus for higher education institutions, RQ3 about the capability levels and recommendations on gaps occurring in higher education institutions. The results of this study find as many as 8 articles consisting of 7 national and international journal articles as well as 1 proceeding article based on the inclusion and exclusion criteria set with a range of publication years from 2020 to 2022. Process areas APO04, APO09, APO12, BIA01, DSS05, MEA01 , MEA02, and MEA03 become the focus of attention for higher education institutions in the implementation of IT Governance. The current level of IT Governance capability at higher education institutions has not reached the capability target with recommendations for improvement in the form of fulfilling activities that have not been implemented at each capability level